As necessidades percebidas pelos alunos de inglês como língua estrangeira no contexto do inglês global - Andrade, Isabel Souto Ottoni de (2014)
The present study aimed to identify the needs perceived by students of English as a foreign language in the context of global English. Recent linguistic studies, as in Rajagopalan, Pennycook and Graddol, have been discussing the role of English language in the current world. Global English embraces several variations of English, not only countries which speak it as a first language, but also countries which speak it as a second language and the others which speak it as a foreign language. Therefore, global English does not refer to only one variation of English language, but to several ways of speaking the idiom throughout the world. Consequently, new concerns regarding the teaching and learning of English and the needs of students have arisen, for example what variation of English should be prioritized when teaching the language. The following questions were the basis of our analysis: 1) What are the needs perceived by the students of English as a foreign language in the context of global English? 1.1) What variations of English language guide the students? 1.2) How do the students perceive English as a global language in different situations? In order to answer these questions, data was collected, through semi structured interviews, from students who learn English in private classes and speak the idiom in different situations, like work, studies and travel. This research is a case study and its data was analyzed according to Bardin and interpreted qualitatively. The results have shown that, although most of the interviewed students say that their need when speaking English is just intelligible communication, there is still an aspiration for specific variations of the language, the idealization of native speakers and the worry about grammar and pronunciation mistakes